IDENTIFIKASI KERENTANAN BANGUNAN DI KOTA LANGSA AKIBAT BAHAYA GEMPA DAN KELAS SITUS - Fajri, Haikal; Irwansyah, Irwansyah; Fahriana, Nina; Basrin, Defry; Al Atas, Zaenal Abidin (JURNAL TEKNIK SIPIL, 2023)
Globally, Aceh Province is an earthquake-prone area, especially earthquakes with an epicenter on land, such as the 2013 in Central Aceh with a magnitude of 6,1; the 2016in Pidie Jaya with a magnitude of 6,5 which damaged more than 10.000 buildings, and killed 85.000 people, according to a report from the Aceh disaster management agency (BPBA).The BMKG recorded an earthquake measuring M 5,3 on 27 September 2018 with the epicenter location on land with a depth of 10 km. Recently on 3 December 2020, an earthquake measuring M 4,9 occurred at a location very close to the previous earthquake. Having this phenomenon, as well as the close distance between the epicenter and the city center, this study aims to identify the risk of vulnerability of residential buildings in the city center to potential earthquakes and class of soil sites (Vs30). The ground motion equation was carried out with scenario of SA to SF soil site class with the epicenter point 22,48 km from the city center at a depth of 10 km. The type of building that has the greatest probability of failure is the C3L, while the sturdiest building is the RM2M type. Therefore, preliminary results indicate that the HAZUS tool has an advantage in estimating the risks and losses that will in the future provide protection to buildings.